2008
DOI: 10.1007/s00253-007-1257-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Clostridium acetobutylicum butanol synthetic genes in Escherichia coli

Abstract: A recombinant butanol pathway composed of Clostridium acetobutylicum ATCC 824 genes, thiL, hbd, crt, bcd-etfB-etfA, and adhe1 (or adhe) coding for acetyl-CoA acetyltransferase (THL), beta-hydroxybutyryl-CoA dehydrogenase (HBD), 3-hydroxybutyryl-CoA dehydratase (CRT), butyryl-CoA dehydrogenase (BCD), butyraldehyde dehydrogenase (BYDH), and butanol dehydrogenase (BDH), under the tac promoter control was constructed and was introduced into Escherichia coli. The functional expression of these six enzymes was prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
186
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(192 citation statements)
references
References 25 publications
2
186
1
3
Order By: Relevance
“…We found that either route led to production of trans-2-pentenoate, suggesting all enzymes examined here, Hbd, Crt, PhaB, and PhaJ1, are able to accept five-carbon substrates. The low titers compared with 3HV synthesis (∼55 mg/L versus ∼2 g/L) also identified dehydratase activity as a potential bottleneck in the full pathway, despite previous reports of high enzyme activities measured in vitro in E. coli extracts (19).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We found that either route led to production of trans-2-pentenoate, suggesting all enzymes examined here, Hbd, Crt, PhaB, and PhaJ1, are able to accept five-carbon substrates. The low titers compared with 3HV synthesis (∼55 mg/L versus ∼2 g/L) also identified dehydratase activity as a potential bottleneck in the full pathway, despite previous reports of high enzyme activities measured in vitro in E. coli extracts (19).…”
Section: Resultsmentioning
confidence: 85%
“…This result was corroborated by the appearance of improved protein expression for the codon-optimized variant by SDS/PAGE analysis. Interestingly, the original AdhE gene has been used previously to produce butanol (6,19,20). This result might point to a lower activity with the C5 substrates, such that improved expression is now more important.…”
Section: Resultsmentioning
confidence: 97%
“…For example, YqhD has a Km value of approximately 0.5 mM for butyraldehyde; this is lower than the reported 1.6 mM for Clostridium acetobuylicum's butyraldehyde dehydrogenase (Palosaari and Rogers 1988) and 4.7 mM for aldehyde dehydrogenase ALDH in Lactobaccilus brevis (Berezina et al 2010). Thus, it seems that the high background level of butyraldehdye reductase activity observed in E. coli by Inui et al could be attributed to YqhD (Inui et al 2008).…”
Section: Unexplored Functionsmentioning
confidence: 98%
“…In another case, E. coli JM109 strain overexpressing the crt, bcd, etfAB, hbd, adhE and thiL genes of C. acetobutylicum was developed. This engineered E. coli strain was able to produce 16 mM butanol using 4% (w/v) glucose as a carbon source [58]. More recently, metabolic engineering has been used for the development of C. cellulolyticum H10 for isobutanol synthesis directly from cellulose [59] (Fig.…”
Section: Consolidated Bioprocessing By Clostridial Speciesmentioning
confidence: 99%